Comparison of Facial Heights Between Iraqi Arab and Kurdish - Hussain A Obaidi; Alaa' D Al-Dawoody; Bayan A Hassan (University of Mosul, College of Dentistry, 2011)
Aims: To investigate for any difference in facial height measurements between Iraqi Arabs and Kurds adolescents. Materials and Methods: lateral cephalometric radiographs Of 42Arabic adolescents in Mosul city and 43 Kurdish adolescents in Arbil city were assessed for anterior and posterior facial height measurements. Results: No significant difference was found in facial height measurements be-tween Arabic males and females. In Kurds, males showed significantly higher facial measurements than females. Kurdish adolescents had significantly greater facial height measurements than Arabic counterparts. Conclusions: Our results revealed that there is an overall difference in the facial height measurements between Arabic and Kurdish Iraqi adolescents